The Modernisation of HIV and AID’s Nomenclatures in Nigeria’s Major Languages (2017)
Although the level of awareness of HIV has significantly improved over the past decade following the coordinated activities of the National Agency for the Control of AIDS (NACA), Nigeria still remains one of the most burdened countries in the world with about 3 million people living with HIV. Increasing enlightenment campaigns on HIV and AIDS have not been able to achieve remarkable behaviour change as a result of the non-use of appropriate nomenclatures. Given the low literacy rate of Nigerians in English (about 61% based on UNESCO Institute for Statistics), communication strategies can only be effective when indigenous Nigerian languages have standardised and appropriate nomenclatures for HIV and AIDS. This study argues that the use of appropriate terms in the local languages in referring to H IV and AIDS is capable of reducing the stigmatisation and discrimination of people living with HIV and AIDS, and con sequently reduce the spread of HIV through behaviour change. Accordingly, the study embarks on the lexical modernisation of H IV and AIDS nomenclatures in Nigeria’s three major languages (i.e. Hausa, Igbo and Yoruba) in line with current developments around the world in the management of the two health conditions.